Analisis dan Penentuan Model Empiris untuk Estimasi Sebaran Klorofil-a menggunakan Citra Satelit Sentinel-2(Studi Kasus: Waduk Saguling, Sungai Citarum) - Tirtana Putri, Aulia; Soewondo, Prayatni; Wijayasari, Winda; Immaddudin Wira Rohmat, Faizal (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The upstream of River Citarum is mildly polluted, which indicates the importance of water river monitoring. This study aims to analyze and determine an empirical model, which is a regression equation using Sentinel-2 satellite imagery to estimate chlorophyll-a concentration in the Saguling Reservoir, upstream of Citarum River. The Multiple Linear Regression (MLR) equation has been obtained, integrating bands 2, 3, 4, 5 and 11 with an R2 value of 0.75 and RMSE of 1.39. However, the results of the model correlation test with validation data indicate a decline in model performance, reflected by an R2 value of 0.261 and RMSE of 4.2. The visualization results using the model with Google Earth Engine (GEE) show an increase in chlorophyll-a concentration in 2024 compared to 2022. However, the actual presence of vegetation in the waters and segmentation errors need to be considered, because they can affect the accuracy of the estimate. This study has limitations in that it only uses reflectance values ​​and chlorophyll-a concentration in situ, without considering other factors. However, the results of the study indicate that the estimated results of the model and the actual values remain within the same range according to their trophic status, suggesting that this model can serve as an overview for predicting chlorophyll-a distribution in the Saguling Reservoir.